2021
DOI: 10.1177/1759720x211002685
|View full text |Cite
|
Sign up to set email alerts
|

Impact of immunogenicity on clinical efficacy and toxicity profile of biologic agents used for treatment of inflammatory arthritis in children compared to adults

Abstract: The treatment of inflammatory arthritis has been revolutionised by the introduction of biologic treatments. Many biologic agents are currently licensed for use in both paediatric and adult patients with inflammatory arthritis and contribute to improved disease outcomes compared with the pre-biologic era. However, immunogenicity to biologic agents, characterised by an immune reaction leading to the production of anti-drug antibodies (ADAs), can negatively impact the therapeutic efficacy of biologic drugs and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 105 publications
(347 reference statements)
0
6
0
Order By: Relevance
“…In general, clinical experiences with receptor Fc-fusion therapeutics have not suggested that cross-reactivity of ADAs with endogenous receptors is a risk for this class of biologics. 17,[28][29][30] This study involved a relatively small number of evaluable participants, and the immunogenicity data were collected for a relatively short period for STELLAR (with median treatment time of 36 months). Moreover, of the 42 participants who were ADA-POS, only 11 had NAbs detected at week 24, and 12 at the end of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, clinical experiences with receptor Fc-fusion therapeutics have not suggested that cross-reactivity of ADAs with endogenous receptors is a risk for this class of biologics. 17,[28][29][30] This study involved a relatively small number of evaluable participants, and the immunogenicity data were collected for a relatively short period for STELLAR (with median treatment time of 36 months). Moreover, of the 42 participants who were ADA-POS, only 11 had NAbs detected at week 24, and 12 at the end of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical experience with sotatercept thus far has not identified any clinical effects suggesting such risk. In general, clinical experiences with receptor Fc‐fusion therapeutics have not suggested that cross‐reactivity of ADAs with endogenous receptors is a risk for this class of biologics 17,28–30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also recognized that antibody therapy may raise the morbidity of unwanted immune response-mediated side effects because of the immunity-modulating nature of antibody function and the potential antigenic activity of exogenous immunoglobulins that are characterized by a high molecular weight as well as a complex structure [ 3 4 ] . Therefore, the ADAs have been identified in up to 60% of autoimmune patients on the treatment of antibodies against tumor necrosis factor-α (TNF-α), including adalimumab, and these ADAs were largely neutralized [ 22 23 ] . Consequently, the anti-TNF-α inhibitor ADAs led to the reduced efficacious outcomes and higher rates of relevant side effects in the clinic [ 23 ] .…”
Section: Antibodymentioning
confidence: 99%
“…The prevalence of ADAs ranges from nearly undetectable in etanercept to 67% in infliximab and adalimumab [ 102 , 103 ]. Factors influencing the emergence of ADAs include genetic predisposition, smoking habits, manufacturing process of bDMARDs, and the prolonged exposure of bDMARDs, in which the last factor is the riskiest [ 104 ]. Serum drug levels are affected by ADAs through various biological mechanisms, such as competitive inhibition or enhanced drug clearance.…”
Section: Introductionmentioning
confidence: 99%